Moebius Syndrome Misdiagnosed as Duane Retraction Syndrome: A Case Report - Harnoor Kaur; Neha K Sethi; Harsimarpreet Singh (Journal of Clinical and Diagnostic Research)
Moebius syndrome and Duane Retraction Syndrome (DRS) are Congenital Cranial Dysinnervation Disorders (CCDDs) characterised as congenital, non progressive groups of diseases caused by abnormal development of cranial nerve nuclei or their axonal connections. Due to their overlapping features, distinguishing between these disorders can be challenging, leading to potential diagnostic oversights. This is a case report of a 10-year-old female with Moebius syndrome misdiagnosed as DRS. She had 6th and 7th nerve palsies with exposure keratopathy. Probably the cause for misdiagnosis was the presence of an abduction deficit-a characteristic shared by both disorders. Additionally, it is crucial to examine the facial nerve, as it is exclusively affected in Moebius syndrome. DRS is significantly more common than Moebius syndrome; the rarity of Moebius syndrome might contribute to the misdiagnosis. Conducting a thorough examination is essential for differentiating between these conditions, thereby facilitating comprehensive management.